2014
DOI: 10.1128/mcb.01647-13
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Pancreas-Specific Oxidoreductin ERO1β in the Pathogenesis of Diabetes Mellitus

Abstract: A growing body of evidence has underlined the significance of endoplasmic reticulum (ER) stress in the pathogenesis of diabetes mellitus. ER oxidoreductin 1␤ (ERO1␤) is a pancreas-specific disulfide oxidase that is known to be upregulated in response to ER stress and to promote protein folding in pancreatic ␤ cells. It has recently been demonstrated that ERO1␤ promotes insulin biogenesis in ␤ cells and thus contributes to physiological glucose homeostasis, though it is unknown if ERO1␤ is involved in the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…It has been proposed that such an increase in insulin biosynthesis leads to accumulation of misfolded and unfolded proinsulin in the ER lumen (42,43) and consequently to the induction of UPR markers such as of the pancreas-specific oxidoreductase ERO-1␤ (11,44), presumably to cope with the increased (pro)-insulin folding demand. However, interestingly, Prdx4 is not induced by ER stress (18,45), indicating that ER stress-mediated induction of the H 2 O 2 -generating ERO-1␤ could have detrimental effects on insulin biosynthesis and glucose-induced insulin secretion as demonstrated recently (46). In addition to its antioxidative action in the ER, it has recently been shown that Prdx4 plays an important role in the oxidation of PDI proteins (19,47).…”
Section: Discussionmentioning
confidence: 87%
“…It has been proposed that such an increase in insulin biosynthesis leads to accumulation of misfolded and unfolded proinsulin in the ER lumen (42,43) and consequently to the induction of UPR markers such as of the pancreas-specific oxidoreductase ERO-1␤ (11,44), presumably to cope with the increased (pro)-insulin folding demand. However, interestingly, Prdx4 is not induced by ER stress (18,45), indicating that ER stress-mediated induction of the H 2 O 2 -generating ERO-1␤ could have detrimental effects on insulin biosynthesis and glucose-induced insulin secretion as demonstrated recently (46). In addition to its antioxidative action in the ER, it has recently been shown that Prdx4 plays an important role in the oxidation of PDI proteins (19,47).…”
Section: Discussionmentioning
confidence: 87%
“…On a different note, an emerging therapeutic concept is to kill solid tumors by redox attack, which is most prominently illustrated by the preclinical success of photodynamic therapies (Garg and Agostinis, 2014), as well as by the use of PDI inhibitors (Higa et al, 2014;Xu et al, 2014). Finally, defective insulin secretion and ER stress that is caused by folding-impaired genetic variants of proinsulin can be rescued by expression of hyperactive Ero1 (Wright et al, 2013), although increasing Ero1 activity in healthy b-cells predisposes them to developing ER stress and diabetes (Awazawa et al, 2014). Thus, targeted ER hyper-oxidation might be a viable therapeutic strategy in a subset of diabetic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Ero1a-derived H 2 O 2 , rather than disulfide overproduction, appears to affect ER homeostasis. Similarly, overexpression of Ero1b in pancreatic b-cells causes ER stress (Awazawa et al, 2014). Whether H 2 O 2 that is derived from endogenous Ero1 is sufficient to trigger ER stress is questionable (Appenzeller-Herzog, 2011;Ramming et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ROS may also be generated as a consequence of a futile cycle of oxidizing and reducing glutathione (GS‐SG and GSH, for oxidized and reduced forms of glutathione, respectively). As a consequence, pancreatic β‐cells, bearing the large load of proinsulin that must assemble 3 disulphide bonds per molecule, may be more susceptible to ER protein misfolding in response to overactivity of various oxidative enzymes . In theory, pancreatic β‐cells could utilize the activity of peroxiredoxin‐4 (PRDX4) to consume H 2 O 2 in the ER in order to make additional proinsulin disulphide bonds and resist ER stress; however, evidence to date has suggested a limited expression of PRDX4 in rodent islet β‐cells, although it becomes induced in islets of rodents upon HFD …”
Section: Dynamic Regulation Of the Er Environment In Repsonse To Succmentioning
confidence: 99%
“…As a consequence, pancreatic β-cells, bearing the large load of proinsulin that must assemble 3 disulphide bonds per molecule, may be more susceptible to ER protein misfolding in response to overactivity of various oxidative enzymes. 185 In theory, pancreatic β-cells could utilize the activity of peroxiredoxin-4 (PRDX4) to consume H 2 O 2 in the ER in order to make additional proinsulin disulphide bonds and resist ER stress 186 ; however, evidence to date has suggested a limited expression of PRDX4 in rodent islet β-cells, 187 although it becomes induced in islets of rodents upon HFD. 188 Interestingly, under certain circumstances, antioxidant treatment can effectively reduce ER stress and subsequent cell death.…”
Section: Er Redox Balance and The Potential Therapeutic Utility Of mentioning
confidence: 99%